Understanding Suboptimal Insulin Use in Type 1 and Type 2 Diabetes: A Cross-Sectional Survey of People with Diabetes - Newson RS; Artime E; Bower J; Spaepen E; Liao B; Bhattacharya I; Battelino T (Patient Preference and Adherence, 2025)
Rachel S Newson,1 Esther Artime,2 Julie Bower,3 Erik Spaepen,4 Birong Liao,3 Indranil Bhattacharya,5 Tadej Battelino6 1Medical Affairs, Eli Lilly and Company, Sydney, New South Wales, Australia; 2VEO, Eli Lilly and Company, Alcobendas, Community of Madrid, Spain; 3Medical Affairs, Eli Lilly and Company, Indianapolis, IN, USA; 4HaaPACS GmbH, Schriesheim, Baden-Württemberg, Germany; 5Medical Affairs, Eli Lilly and Company, Gurgaon, Haryana, India; 6University Medical Center Ljubljana, and Faculty of Medicine, University of Ljubljana, Ljubljana, SloveniaCorrespondence: Rachel S Newson, Real World Evidence, Eli Lilly and Company, 60 Margaret Street, Sydney, NSW, 2000, Australia, Email newson_rachel@lilly.comPurpose: This analysis aimed to document suboptimal insulin dosing (missed or skipped and mistimed basal and/or bolus) in people with diabetes (PwD), including type 1 diabetes (T1D) and type 2 diabetes (T2D). Additionally, barriers and solutions for optimal insulin dosing were explored.Patients and Methods: This multinational, cross-sectional, online survey was conducted in the United States, the United Kingdom, and Germany. Eligible PwD with T1D or T2D used an analog insulin pen. Data were analyzed using descriptive statistics.Results: A total of 1150 PwD (T1D: 300; T2D: 850) were included. Overall, a proportion of PwD reported missing 1 or more basal (48.2%) or bolus dose (59.6%) in the past 30 days. Among those who reported missing doses, the average number [standard deviation] was 3.6 [3.6] basal doses and 4.6 [7.4] bolus doses. PwD reported forgetting, being too busy/distracted, and finding it too complicated or burdensome as key reasons for missed doses. A proportion of PwD reported mistiming 1 or more basal (45.7%) dose or bolus (53.6%) dose in the past 30 days. Among those who reported mistiming doses, the average was 3.9 [4.0] basal and 5.1 [8.1] bolus doses. Key reasons reported for mistiming doses included being too busy or distracted, being out of routine, or having an unexpected or earlier/later-than-expected meal.Conclusion: Suboptimal insulin use is prevalent among PwD, with nearly half of participants reporting missed or mistimed doses in the past 30 days. Results indicate the need for support to help PwD self-manage the complexity of insulin treatment and to improve outcomes due to suboptimal insulin dosing. Such support might include devices that record measurements and dosing and provide feedback.Keywords: diabetes, basal, bolus, suboptimal dosing, missed doses, mistimed doses